Perlindungan Finansial Istri dari Kepailitan Suami: Signifikansi Perjanjian Perkawinan Pasca Putusan MK No. 69/PUU-XIII/2015 - Ai Siti Nurbaitilah; Yudi Wahyudin; Abdul Kodir Alhamdani; Encum Sumirah; Sisca Lestari (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2026)
A husband’s bankruptcy carries serious legal consequences for joint marital property, whereby all joint assets are included in the bankruptcy estate under Article 64 paragraph (1) jo. Article 23 of Law Number 37 of 2004, placing the wife in a financially vulnerable position. This study aims to analyze the significance of marriage agreements following the Constitutional Court Decision Number 69/PUU-XIII/2015 as an instrument for the wife’s financial protection from the husband’s bankruptcy, examine its legal implications on the status of joint property in bankruptcy cases, and formulate an ideal legal construction for the wife’s financial protection. This study employs a normative legal research method with statutory and conceptual approaches. The findings demonstrate that the Constitutional Court Decision holds fundamental significance as it opens opportunities for married couples without marriage agreements to establish asset separation agreements during the marriage, thereby protecting the wife’s assets from the husband’s bankruptcy estate. However, the effectiveness of such agreements is limited by requirements including notarial deed formalization, registration with authorized institutions, non-prejudice to third parties, and good faith. Agreements made to transfer assets solely to avoid bankruptcy may be declared null and void. Harmonization of regulations between marriage law, bankruptcy law, and Islamic family law, along with massive public socialization regarding the urgency of marriage agreements as preventive measures for family asset protection, is necessary.